EFFECT OF DIFFERENT LEVELS OF PLANT GROWTH REGULATORS ON GROWTH AND YIELD OF BLACKGRAM (Vigna mungo L.) - BODDU REDDY REVANTH; VIKRAM SINGH; DHANANJAY TIWARI (The Bioscan, 2021)
An experiment was conducted during Kharif-2019 at crop research farm of SHUATS, Prayagraj to study the effect of plant growth regulators on growth and yield parameters of Blackgram. The study was carried out in randomized block design with 3 replications and 9 treatments of NAA (10, 20, 40 ppm), GA 3 (50, 100, 150 ppm) and salicylic acid (50, 100, 150 ppm) with foliar application at 25, 35 and 45 DAS respectively. Results indicated that application of Salicylic acid 150 ppm at 45 DAS, significantly recorded higher growth, yield, net returns and was found to be promising than other treatments. The recorded results with the same are as plant height (43.73cm), Dry weight (3.46g), number of nodules (19.12), pods per plant (42.13), grains per pod (12.20), grain yield (746 kg/ha), stover yield (2478 kg/ha), gross return( Rs 44460/ha), net returns (Rs 22679.10/ha) and benefit cost ratio 2.04. The study concluded that application of Salicylic acid 150 ppm at 45 DAS was productive as well as economic.